Exploration and practice of the “SPOC+PAD class” blended teaching model in the course of epidemiology - Yang, Haomin; Fu, Rong; Lin, Tao; He, Fei (Frontiers in Education, 2025)
BackgroundThe blended teaching model of “online theory + offline practice” has become a focal point in the new era of medical education. However, the combination of Small Private Online Course and Presentation-Assimilation-Discussion (SPOC+PAD) classroom has not been practiced in Epidemiology courses.MethodsTo thoroughly evaluate the “SPOC+PAD” blended teaching model, this study included 56 students from a medical university, who selected the course Medical Statistics and Epidemiology in Fujian Province, China. Written final exam scores, lifelong learning abilities and collaboration skills were assessed and compared using t test between 25 students with “SPOC+PAD” teaching model and 31 students with “SPOC” only model. A multivariable linear regression model was further conducted to examine the factors influencing final exam score.ResultsIn the final exam for epidemiology, the mean score of students with “SPOC+PAD” was 35.20 ± 6.17 points, slightly higher than that of students with SPOC only (32.29 ± 6.61 points). Students' gender is a key factor affecting final exam scores. Among female students, compared with SPOC teaching, the “SPOC+PAD” blended teaching model can significantly improve final exam score (P = 0.038). However, the role of this teaching model in enhancing students' lifelong learning ability and collaboration skills was not significant.ConclusionsCompared with SPOC teaching, the “SPOC+PAD” blended teaching model can improve the study outcomes, especially in female students. Evaluation of lifelong learning ability and collaboration skills may require further study with larger sample sizes and longer teaching cycles.